Agglomeration, Congestion, and Regional Unemployment Disparities - Ulrich Zierahn (European Regional Science Association (ERSA), 2011)
Regional labor markets are characterized by huge disparities of unemployment rates. Models of the New Economic Geography explain how disparities of regional goods markets endogenously arise but usually assume full employment. This paper discusses regional unemployment disparities by introducing a wage curve based on efficiency wages into the New Economic Geography. The model shows how disparities of regional goods and labor markets endogenously arise through the interplay of increasing returns to scale, transport costs, congestion costs, and migration. In result, the agglomeration pattern might be catastrophic or smooth depending on congestion costs. The transition between both patterns is smooth.
Keywords: 330